The Impact Of Commercial Development Of The Reservation Environment In The German Investigation - Nafa C Husana Devi; Gusti A Maulida; Bayu P Perdana; Miftahul Akbar N.A; Reksy Hendrawan (ESE International Journal (Environmental Science and Engineering), 2018)
Current development is increasingly prevalent in areas especially in urban areas, such buildings can be either residential buildings or trade and services that can improve the economy, be it for the government or for the surrounding community but also often development can have an impact on the environment so that causing problems of such development as in some commercial buildings on Jalan Sutoyo S Kelurahan Teluk Dalam Banjarmasin Tengah grew in tandem with increasing settlements. These developments trigger socio-cultural and economic activities, so the settlements on the outskirts (access) prefer to open businesses to improve their economy. Known by the influence of such commercial development on the surrounding settlements, there has been changes to the environment, and comfort. With this concluded that the influence of commercial pembagunan both positive or negative impact. For that we need an effort for commercial development, so as not to harm all aspects of social, economic and environmental.